Waterborne agrichemicals compromise the anti-predatory behavior of zebrafish - Pompermaier, Aline; Kirsten, Karina; Soares, Suelen Mendonça; Fortuna, Milena; Kalichak, Fabiana; Idalencio, Renan; Koakoski, Gessi; Barreto, Rodrigo Egydio [UNESP]; Barcellos, Leonardo José Gil (Springer Nature, 2020)
Due to human activities, there is an increasing presence of agrochemicals residues in water bodies, which could be attributed to an increased use of these chemicals, incorrect disposal of packaging materials, and crop leaching. The effects of these residues on prey-predator relationship of aquatic animals are poorly known. Here, we show that fish acutely exposed to glyphosate, 2,4-D, and methylbenzoate-based agrichemicals have their anti-predatory responses impaired. We exposed zebrafish to sub-lethal concentrations of agrichemicals and evaluated their behavioral reaction against a simulated bird predatory strike. We observed that agrichemical-exposed fish spent more time in a risky area, suggesting that the pesticides interfered with their ability of risk perception. Our results highlight the impairment and environmental consequences of agrochemical residues, which can affect aquatic life and crucial elements for life (food web) such as the prey-predator relationship.
Keywords: 2,4-D; Danio rerio; Environmental contamination; Glyphosate; Methylbenzoate; Pesticide residues; Prey-predator relationship